Sports Injuries 2011
DOI: 10.1007/978-3-642-15630-4_153
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Strengthen the Quadriceps Femoris in Patients with Patellofemoral Pain Syndrome?

Abstract: SummaryPurpose: the aim of this article was to review the clinical approach of quadriceps strengthening programmes. Methods: a literature search was carried out from 1980 up to September 2011. Eligible studies were those that: (1) evaluated the patients with patellofemoral pain syndrome (not healthy or asymptomatic subjects) (2) examined the effect of kinetic chain exercises (3) examined the effect of weight-bearing exercises (4) compared the effect of the combined exercises programme in the treatment of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…1,9,12,18,27 Both forms of exercise have their advantages with respect to quadriceps strengthening. Weight bearing exercises are more functional in nature 7,11 and incorporate contractions of multiple agonist and antagonist muscle groups.…”
mentioning
confidence: 99%
“…1,9,12,18,27 Both forms of exercise have their advantages with respect to quadriceps strengthening. Weight bearing exercises are more functional in nature 7,11 and incorporate contractions of multiple agonist and antagonist muscle groups.…”
mentioning
confidence: 99%
“…However, the behavior of the spin polarization P EC S (black circles) is shifted by about 45 deg with respect to the MOKE data. Hence, the maximum and minimum of P EC S were not along VEA1 rather than along an axis, named here surface easy axis (SEA), oriented 10 deg next to the <110> directions, which are the medium axes for Ni [3]. This shift we found for slow as well as fast (pulsing) current change (cf.…”
mentioning
confidence: 63%
“…The two opposite directions along an easy axis are usually equivalent, and the actual direction of magnetization can be either of them. The orientations of the easy and hard axes of the elemental 3d-Ferromagnets Fe, Co and Ni were experimentally well established [1][2][3]. The easy axes are <100> for Fe, <0001> for Co and <111> for Ni.…”
mentioning
confidence: 99%
“…This study is the first to demonstrate the functional hyperextension lack and absence of the patellar dimple sign in female patients with patellofemoral pain syndrome. It is needed that future studies might investigate patellar dimple using leg extension test 18 , isokinetic test for muscle strength 19 , functional MRI (fMRI) for patellar position and patellar dimple sign during activities, movement analyses for the knee angles, and electromyographic (EMG) actions 18 for vastus medialis and vastus lateralis during activities. It is also suggested that future studies might look at the effect of functional hyperextension knee exercises/techniques and look at the longer term follow-up of these patients.…”
Section: Resultsmentioning
confidence: 99%